An evaluation of an after-school programme for high school learners in Cape Town, South Africa - Benkenstein, Alex (Institute for Monitoring and Evaluation, 2017)
Poor academic achievement in relation to developing country peers, together with a range of other issues such as violence in schools, high drop-out rates and high teenage pregnancy rates, contribute to the perception of a crisis in South African education. In this context, after-school programmes have been developed in order to supplement the education and support learners receive during school. There is a large and growing body of literature which supports the view that after-school programmes can deliver positive outcomes, particularly for low-income students. Such positive outcomes, however, are far more likely to be observed with high quality programmes. This study presents an outcome evaluation of the EduCentre programme, an after-school programme targeted at high school youth. The EduCentre is implemented by a nonprofit organization in Vrygrond, a low-income community situated 25km south of Cape Town's central business district near the suburb of Muizenburg. The research design is pre-experimental and is based on the Success Case Method (Brinkerhoff, 200). A survey of a selected cohort of programme participants were surveyed in order to assess perceptions around programme design and impact, as well as assessing social and emotional skills. Following the Success Case Method, interviews were subsequently conducted with selected 'success' and 'non-success' cases, supplemented by interviews with programme staff. The study concludes that, within the limits of the pre-experimental methodology, there is evidence for the beneficial impact of the programme. The study concludes with recommendations to support programme design and future monitoring and evaluation efforts.